Determination of Toxic Elements in Tobacco, Tobacco Smoke and Ash from Selected Imported Cigarettes Brands - Al-Dahhan, Wedad; Hashim, Hassan; Ibraheem, Hanan; Yousif, Emad; Hadi, Hussein M (Al-Nahrain Journal of Science, 2018)
Metals are essential to the human body but can be harmful to health when it exceeds permissible limits. Different sorts of cigarettes were chosen from the markets in Iraq to conduct the tests of the elements in these species. The chose samples were tested using EDX instrument. Results demonstrated the presence of the proportions of dangerous elements such as (Sb, Ni, Zn, P, Pb, Cd, Ca, Si, S, Cr, Mg, Na, As, Al, Cl, and Sn), which greatly affect the health of the smoker and its negative effects to the environment. The genuine risk is the result of accumulate these elements in the body of the smoker’s lungs, liver, blood or brain and its effects are chronic and more dangerous and threatens the life of the person in the future. A special absorption system was used to absorb tobacco smoke for the tested samples by deionized water. The remaining ash collected for acid digestion and prepared to atomic absorption analyses.